2021
DOI: 10.2147/ijgm.s320115
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastographic Findings in Clubfeet

Abstract: Purpose One of the main features of congenital idiopathic clubfoot is the increased stiffness of soft tissues. With the growing popularity and availability of sonoelastography as a method to assess the stiffness of different tissues, we considered applying it to congenital clubfeet in order to to determine whether sonoelastography can be a useful imaging method for the evaluation of clubfeet, to assess whether there are any differences in stiffness of specific tendons between clubfeet and normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Based on these features, sonoelastographic examination of the Achilles tendon has been performed in many diseases in the literature and the relationship between the disease and the measurements has been evaluated. [12][13][14][15][16][17] It has been concluded that in addition to rheumatological diseases, there are subclinical changes in sonoelastography in the Achilles tendon in metabolic and structural musculoskeletal system problems, which can be useful in predicting the prognosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these features, sonoelastographic examination of the Achilles tendon has been performed in many diseases in the literature and the relationship between the disease and the measurements has been evaluated. [12][13][14][15][16][17] It has been concluded that in addition to rheumatological diseases, there are subclinical changes in sonoelastography in the Achilles tendon in metabolic and structural musculoskeletal system problems, which can be useful in predicting the prognosis of diseases.…”
Section: Discussionmentioning
confidence: 99%